An immediate derivation of maximum principle in Banach spaces, assuming reflexive input and state spaces - D‘alessandro, Paolo (CUBO, A Mathematical Journal, 2012)
We consider a standard setting for the norm optimal problem in Banach spaces and show that with a simple argument which invokes some appropriately selected powerful general Theorems for Banach spaces a straightforward derivation of the Maximum Principle is obtained.